2015
DOI: 10.3923/ajppaj.2015.83.90
|View full text |Cite
|
Sign up to set email alerts
|

Serological Screening of Cowpea Genotypes for Resistance against Cowpea Aphid Borne Mosaic Virus Using DAS-ELISA

Abstract: Cowpea (Vigna unguiculata (L.) Walp), an important protein rich arid legume crop is susceptible to number of fungal, bacterial and viral diseases that severely limit the productivity. A set of 92 diverse cowpea genotypes including varieties, mutants, advanced breeding lines, exotic and indigenous collections were serologically screened for resistance against Cowpea Aphid Borne Mosaic (CABM) virus using DAS-ELISA. The genotypes grown in triplicate in a randomized block design at Trombay were mechanically inocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…The differences in the levels of prevalence of CMV, CPSMV and CMV in the cowpea genotypes could be explained on the basis of antagonism, inoculum level, the age of the plant, climatic conditions and cultivar type (Orawu et al, 2015). The varying reactions of the cowpea genotypes to different cowpea viruses observed in the present study is quite valuable because it will enable breeders to breed for resistance against viruses that prevail at a particular location, as reported by Dhanasekar and Reddy (2015). The presence of viruses in a combination may result in synergism or antagonism effects within the infected plants.…”
Section: Incidence and Severity Of Viruses On Selected Cowpea Genotypessupporting
confidence: 53%
See 2 more Smart Citations
“…The differences in the levels of prevalence of CMV, CPSMV and CMV in the cowpea genotypes could be explained on the basis of antagonism, inoculum level, the age of the plant, climatic conditions and cultivar type (Orawu et al, 2015). The varying reactions of the cowpea genotypes to different cowpea viruses observed in the present study is quite valuable because it will enable breeders to breed for resistance against viruses that prevail at a particular location, as reported by Dhanasekar and Reddy (2015). The presence of viruses in a combination may result in synergism or antagonism effects within the infected plants.…”
Section: Incidence and Severity Of Viruses On Selected Cowpea Genotypessupporting
confidence: 53%
“…Viruses are a major biotic constraint to cowpea production, reported to bring about yield losses ranging from 10 to 100% (Dhanasekar and Reddy, 2015). Over 140 viruses worldwide have been reported to attack cowpea and at least 11 of these occur in Africa (Hughes and Odu, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IITA reported that one of its 2003 milestones was the initiation of field testing of transgenic cowpea plants. Cowpea lines resistant to CABMV have been identified (Dhanasekar and Reddy, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…IITA reported that one of its 2003 milestones was the initiation of field testing of transgenic cowpea plants. Cowpea lines resistant to CABMV have been identified (Dhanasekar and Reddy, 2015).…”
Section: Discussionmentioning
confidence: 99%